Work-life balance of women entrepreneurs in Sri Lanka. - Siyam, N.; Kailasapathy, Pavithra (My University, 2021)
In Sri Lanka, female entrepreneurship is contributing towards the economy. However, women entrepreneurs seem to struggle between the two distinct roles: one at work and the other at home which make them difficult to achieve work-life balance (WLB). Hence, the main aim of this study was to enrich the understanding of women entrepreneurs’ WLB in Sri Lanka by drawing on work/family border theory. The research was designed to understand the meaning of WLB from the perspective of women entrepreneurs, to examine the factors affecting their WLB, and to identify how they manage their dual responsibilities at work and home. A qualitative research approach and semi-structured interviews were used. Purposive sampling was used to select 12 women entrepreneurs from micro, small and medium-sized enterprises across industries. This study found three meanings of WLB from the perspective of women entrepreneurs. They are: harmony between work and life, felicity in life, and dynamic with priorities. It identified four factors that influenced the WLB of women entrepreneurs. They are workload and work pressure, childcare, lack of time, and blurring of borders. Finally, it identified that women entrepreneurs use support system and coping strategies to manage their dual responsibilities. Support system comprised of family support, spousal support, and staff support. The coping strategies comprised of planning, scheduling and organizing, networking, and time-offs and breaks. The study also supports the border theory by identifying that segmentation creates synergy in domain responsibilities of women entrepreneurs and blurring of borders would create more work-life balance issues because of greater permeations across borders. Further, we identified that the support from border keepers (e.g., spouse) and other domain members (e.g., sibling) would enhance the WLB of women entrepreneurs by assisting their domain responsibilities. Thus, segmentation and support system can be used to achieve greater WLB.
Keywords: work-life balance; women entrepreneurs; qualitative research; border theory